The role of product knowledge on purchase intention: Case study of agriculture biological product - Felicia Devina Arum Andita; Daniel Hermawan (Institute of Computer Science (IOCS), 2023)
This study aims to find out how companies provide product knowledge to consumers and find out how much influence the delivery of product knowledge has on the emergence of purchase intention in consumers. This research uses mixed methods with a sequential design, starting from quantitative by using a questionnaire and qualitatively by using interviews. The population in this study were all farmers in Caturharjo Village, Pandak District, Bantul Regency, Yogyakarta Special Region. The sampling technique used was non-probability sampling with purposive sampling. From these respondents, data was collected using a questionnaire. The technique in this study uses statistical data analysis techniques with validity tests, reliability tests, normality tests, heteroscedasticity tests, multicollinearity tests, and multiple linear regression analysis, in addition to knowing the effect partially and simultaneously using t-test and F-test. In addition, interviews were conducted with the two heads of farmer groups. This study shows that all dimensions of the product knowledge variable have a positive and significant effect on purchase intention. Of these three dimensions, objective knowledge is the most influential factor in purchase intention. PT. Prosper Biotech Indonesia should maintain a relationship with farmer groups in conducting counseling that conveys material about these products, because these extension workers will grow product knowledge that potential consumers have about their interest in buying products produced by the company. From there, farmers know about ValdisGROW products objectively.